Študij Ni-Cr tankih plasti z elektronsko mikroskopijo - Irmančnik-Belič, Lidija (Kovine zlitine tehnologije, 1997)
A few nm-thick Ni-Cr layer forms the capacitance humidity sensor electrodes. The electrodes must have the adequate electric resistance, low mechanical tensions and proper elasticity coefficient in order to prevent the corruption of the Ni-Cr - dielectric layer joint when the dielectric is saturated by the water vapour. The upper electrode must be permeable for the water vapour in order to permit the water vapour to diffuse into the dielectric. The sufficient permeability of the Ni-Cr film is obtained by an evaporation under the incidence angle 75°. The deposition angle is defined as the angle between the normal of the substrate and the normal of the evaporating source. The obtained results of Ni-Cr layer analysis by the AES, AFM and TEM are presented. The thin Ni-Cr layer is nonhomogeneus due to the different vapour pressure of the Ni and Cr during the deposition process. The Ni-Cr thin film evaporated under 0° incidence angle is cracky, while the layer evaporated under 75° incidence angle has the columnar structure.
Keywords: tanke plasti; nikelj; krom; morfologija; elektronska mikroskopija